Characterizing the Impact of Atmospheric Rivers on Aerosols in the Western U.S. Issue 7 (5th April 2022) - Hu, Zhiyuan; Zhao, Chun; Leung, L. Ruby; Du, Qiuyan; Ma, Yuanyuan; Hagos, Samson; Qian, Yun; Dong, Wenjie
Abstract: Two 5‐year (2010–2014) quasi‐global simulations using the Weather Research and Forecasting model coupled with Chemistry have been analyzed to quantify the impacts of atmospheric rivers (ARs) on aerosols in the western United States (U.S.). We find that AR days have reduced trans‐Pacific as well as U.S. aerosol mass because of enhanced rainfall and hence, wet removal of aerosols, compared to non‐AR days. ARs reduce trans‐Pacific aerosol mass through the cyclonic circulation that shifts the aerosol transport pathway southward and brings cleaner air from the north. However, ARs have larger impact on aerosols that originate over the U.S., which are concentrated closer to the surface compared to trans‐Pacific aerosols that are distributed more uniformly with altitude. While dust and sulfates dominate the mass for both trans‐Pacific and U.S. aerosols, ARs reduce dust composition fractions of trans‐Pacific aerosols but the AR impacts on composition fractions of U.S. aerosols are more variable. Plain Language Summary: Aerosols can be transported by strong westerlies across the North Pacific and reach North America all year around. These transported aerosol particles have been found to interact with the North Pacific atmospheric rivers (ARs). Generally, the aerosol particles from long‐range transport can influence ice nucleation in mid‐level orographic clouds and precipitation forming processes. On the other hand, trans‐Pacific transported aerosols may also be significantly influenced by the synoptic conditions during the AR days. However, the impacts of atmospheric rivers on trans‐Pacific aerosols over the western United States (U.S.) are not well understood. This study illustrates the aerosol distributions during the AR events and shows that ARs can reduce the trans‐Pacific and U.S. aerosols through the enhanced rainfall. Also, ARs can reduce trans‐Pacific aerosol mass through cyclonic circulation. Further, the impacts of ARs on the contribution of trans‐Pacific aerosol over the west coast of North America is positive, which is dominated by dust, followed by sulfate. However, the impacts of ARs on aerosol component fractions from the U.S. are more complicated. These results can give us some new insight into the impacts of ARs on the long‐range transported aerosols. Key Points: The impacts of atmospheric rivers (ARs) on aerosols in western United States (U.S.) are quantified using two 5‐year quasi‐global Weather Research and Forecasting model coupled with Chemistry simulations ARs reduce trans‐Pacific aerosols through precipitation and cyclonic circulation and have larger reduction on dust composition fractions ARs reduce U.S. aerosols because of the enhanced precipitation, but the impacts on composition fractions are more variable